BUILDING MATERIALS INDUSTRIAL PRODUCTION EXTRACTION ECONOMIC EFFICIENCY INCREASING ISSUES (Intent Research Scientific Journal, 2023)
The article highlights issues of increasing the economic efficiency of enterprises producing construction materials, including rising costs, limited resources and increased competition in the industry.